Factorial study of the morphological and physiological requirements of soccer players according to the play compartments - yaaqoub.cheikh (sports creativity, 2025)
The standards of construction and body composition and the requirements of the physical and functional football player affected by the training for this the purpose of this study was to determine the construction and composition of football players according to the game compartments and to identify the nature of the factorial construction we used the descriptive approach with a sample of 225 players as well as using a set of tests and measurements and the results were processed using spss and we arrived to determine a battery of tests represents an overall description of the body structure and composition, in the end we recommend that you use this battery in the selection of football players and for the determination of the game compartments.